Cosy Auditor-Management Relationships and Corporate Frauds in India - Santhosh Kumar, S. (Prabandhan: Indian Journal of Management, 2015)
Corporate accounting frauds are increasing in India. The unholy nexus between auditors and managements is allegedly the key reason for the rising trend in the country. Though the Satyam scandal (2009), the largest corporate fraud in the history of the country, spurred thorough audit checks, the series of frauds alleged thereafter call for more improved measures for prevention. The recent probes by Serious Frauds Investigation Office (SFIO), the investigation arm of the Ministry of Corporate Affairs (MCA) in India, into the alleged frauds since 2008 in 83 companies is quite evident for the signalling scenario in the country. Auditors’ involvement in different forms in these frauds have been seriously deliberating in the country demanding measures to curb the situation. The very recent move in the new Companies Bill for the formation of National Financial Reporting Authority (NFRA) to look after the quality of audit, compliance by auditors, and also the disclosures they make is a significant move in the direction to remedy the situation. Alarmed by the magnitude of the situation, the capital market regulator SEBI (Securities and Exchange Board of India), insurance regulator IRDA (Insurance Regulatory and Development Authority), and telecom regulator TRAI (Telecom Regulatory Authority of India) have also been indulging in severe measures to improve the situation. It is in this context that the paper sheds light on the selected scandals to dig out the involvement of the auditors in these scandals.